2021
DOI: 10.1097/nor.0000000000000787
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Nurse Navigator-Led Preoperative Education on Hospital Outcomes Following Posterolateral Lumbar Fusion Surgery

Abstract: Beyond the spine-specific pathology, patient factors such as associated medical and psychosocial conditions, understanding of the treatment process, and the degree of patient activation—defined as the ability of the individual to utilize the available information and actively engage in making their healthcare decisions—can influence outcomes after posterolateral lumbar fusion (PLF) surgery. A retrospective observational cohort study of 177 patients undergoing PLF at a single institution was conducted. Patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Therefore, these patients may benefit from close monitoring and additional postoperative support from resources such as nurse navigators because these services have been demonstrated to reduce complications and readmissions in spine surgery populations. 28 However, the presence of concomitant LEOA should not be considered a contraindication to surgical treatment because these patients experienced similar improvements in physical function as those without these comorbid conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these patients may benefit from close monitoring and additional postoperative support from resources such as nurse navigators because these services have been demonstrated to reduce complications and readmissions in spine surgery populations. 28 However, the presence of concomitant LEOA should not be considered a contraindication to surgical treatment because these patients experienced similar improvements in physical function as those without these comorbid conditions.…”
Section: Discussionmentioning
confidence: 99%
“… 41 42 43 44 At our institution, recently published data found that patients attending nurse navigator–led preoperative education courses experienced shorter lengths of stay, decreased cost of care, and decreased postacute resource utilization in the total joint and lumbar fusion populations. 45 , 46 Given the potential for suboptimal outcomes in patients with lower extremity OA undergoing lumbar fusion, we suggest all these patients be managed through a nurse navigator. Furthermore, although nurse navigation currently focuses on optimizing patients during the perioperative period, a paradigm shift toward using navigators longitudinally may improve patient engagement and enhance access to appropriate specialists in patients suffering from multiple musculoskeletal diseases.…”
Section: Discussionmentioning
confidence: 99%